Political Leadership in Malaysia - Ku Halim, Ku Hasnan; Mohd Ainuddin Iskandar Lee Abdullah; Jamal Rizal Razali; Sharifudin Abdullah; Suhaimi Sulaiman; Ahmad Mujahid Ahmad Zaidi; Zahrul Akmal Damin (Human Sustainability Procedia, 2024)
This study was conducted to clarify and elaborate on the question of nationalism and political leadership in Malaysia, aimed at justifying the analysis in relation to the phenomenon of political leadership split from the perspective of nationalism. The ethnic diversity that exists in Malaysia makes it difficult to describe the relationship between the diversity of ethnic-identities and national-identities institutionally. However, from another point of view, the question of national-identity that is still not found or there is still no solution can be analyzed or understood through the perspective of the conflict between nationalism-collective and nationalism-individualistic. The political elite or the ruling party, which often plays the role of ’the spokesman’ to the whole of Malaysian society, regardless of race or ethnic background, is seen as a group that highlights this nationalist-collective perspective. The findings of this study are expected to provide an overview of the current scenario of political leadership in Malaysia.